Learning styles, personality types and reading comprehension performance. - Sadeghi, Nabiollah; Mohd Kasim, Zalina; Tan, Bee Hoon; Abdullah, Faiz Sathi (Canadian Center of Science and Education, 2012)
This study aims at reviewing the relationship between learning styles, personality and reading comprehension performance. In the last two decades, ample studies have been done to examine the relationship between learning styles, learner’s personality and performance in academic settings. The reviewed studies substantiate that there is a relationship between personality types and/or traits of the learners, the way they establish their learning styles and their academic success in school and university both at an undergraduate and postgraduate level. Therefore, learners depending on the type of their personality resort to different learning styles or preferences which-in turn- affect their learning performance. However, there are no studies – either theoretical or empirical – examining exclusively the role of personality and learning styles on reading comprehension performance.